Gaps in cancer care in a multi-ethnic population in Sarawak, Borneo : A central referral centre study - Melissa Lim, Siaw Han; Voon, Pei Jye; Adibah, Ali; Fitri Suraya, Mohamad; Lin, Jong; Chew, Lee Ping; Mohamad Adam, Bujang; Yolanda, Augustin; Cheng, Yuong Kang (PLOS, 2024)
Background